Sustained treatment‐free remission in chronic myeloid leukaemia is associated with an increased frequency of innate CD8(+) T‐cells. (12th March 2019) - Cayssials, Emilie; Jacomet, Florence; Piccirilli, Nathalie; Lefèvre, Lucie; Roy, Lydia; Guilhot, François; Chomel, Jean‐Claude; Leleu, Xavier; Gombert, Jean‐Marc; Herbelin, André; Barbarin, Alice
Summary: Immunological mechanisms of treatment‐free remission (TFR) in chronic myeloid leukaemia (CML) are poorly defined and, to date, no correlation between successful TFR and CD8(+) T‐cell subsets has been found. We analysed a new identified human subset of CD8(+) T‐cells, namely innate CD8(+) T‐cells, in CML patients with TFR ≥ 2 years. We demonstrated a dramatic increase of functionally active innate CD8(+) T‐cells in these patients as compared to control subjects and patients in remission under tyrosine kinase inhibitors. Moreover, we found a positive correlation between frequencies of innate CD8(+) T‐cells and natural killer cells, possibly representing a new innate biomarker profile of successful TFR.